Information System for Wedding Service Ordering Based on Web: Sistem Informasi Pemesanan Jasa Acara Pernikahan Berbasis Web - Baharsyah, Muhammad Ronaldo; Astutik, Ika Ratna Indra (JOINCS (Journal of Informatics, Network, and Computer Science), 2021)
Wedding Organizer itself is one of the special services that helps the bride, their families in planning and supervising the implementation of the entire events of the wedding plan according to a predetermined schedule from the wedding ceremony, traditional ceremonies, aisles, etc. Such as the Imagine Wedding Organizer which is one of the cases in this study. In Imagine Wedding Organizer, the system used is still manual. Therefore, in this final report the author provides suggestions in the form of ordering web-based computerized Wedding Event Services. Where the system design uses Unifeld Modeling Language (UML) with the Hypertext Preprocessor (PHP) programming language, MYSQL database, and uses the Waterfall system development method and uses a system testing method called the BlackBox Testing Method. The result of this research is the establishment of a WEB-based Wedding Event Service Ordering Information System on Imagine Organizer. With the establishment of this system is expected to make it easier for customers to place orders.